1996
DOI: 10.1143/ptp.95.1009
|View full text |Cite
|
Sign up to set email alerts
|

Light Vector Mesons in Nuclear Matter

Abstract: We summarize the current theoretical and experimental status of the spectral changes of vector mesons ($\rho$, $\omega$, $\phi$) in nuclear medium. Various approaches including QCD sum rules, effective theory of hadrons and bag models show decreasing of the vector meson masses in nuclear matter. Possibility to detect the mass shift through lepton pairs in $\gamma-A$, $p-A$ and $A-A$ reactions are also discussed.Comment: 33 pages, latex, 14 figures, invited paper (Prog. Theor. Phys.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
101
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 35 publications
6
101
0
Order By: Relevance
“…The medium modification for φ-meson mass occurs due to their coupling to the hyperons, as they do not couple to the nucleons by OZI rule [11]. It is observed that the medium modification of the φ-meson mass is rather small as compared to the mass of the vector ω.…”
Section: In-medium Masses For ω and ρ Vector Mesonsmentioning
confidence: 93%
See 4 more Smart Citations
“…The medium modification for φ-meson mass occurs due to their coupling to the hyperons, as they do not couple to the nucleons by OZI rule [11]. It is observed that the medium modification of the φ-meson mass is rather small as compared to the mass of the vector ω.…”
Section: In-medium Masses For ω and ρ Vector Mesonsmentioning
confidence: 93%
“…This Feynman part of the self energy, Π µν F is divergent and needs renormalization. For the ω meson, the tensor coupling is generally small as compared to the vector coupling to the nucleons [11], and hence is neglected in the present work. We use dimensional regularization to separate the divergent parts.…”
Section: In-medium Masses For ω and ρ Vector Mesonsmentioning
confidence: 99%
See 3 more Smart Citations